P07.23 Evaluation of the cobas® hsv 1 and 2 test for the detection of hsv from clinician-collected anogenital lesion swab specimens compared with elvis® hsv id and d³ typing test and sanger sequencing. (13th September 2015) - Young, S; Van Der Pol, B; Taylor, S; Fife, K; Hook, E; Patel, R; Ding, K; Hemyari, P; Duncan, J; Tang, S; Liesenfeld, O; Osiecki, J; et al.
Abstract : Introduction: Diagnosis of anogenital herpes is definitively established by testing anogenital lesion specimens from symptomatic patients by culture or molecular methods. The objective of this study was to evaluate the cobas ® HSV 1 and HSV 2 Test using clinician-collected swab specimens from external anogenital lesions as part of a large multicenter clinical trial conducted in the United States of America. Methods: Two swabs were collected from patients with possible HSV infection at 8 geographically diverse sites. The first swab was used for culture by the ELVIS ® HSV ID and D³ Typing Test (Diagnostic Hybrids, Inc., Athens, OH) and PCR followed by Sanger sequencing for HSV-1 and HSV-2. The second swab was for the cobas ® HSV 1 and 2 Test. Sensitivity and specificity were calculated compared to the combined results of culture and Sanger sequencing using the "any positive rule". The positive (PPA) and negative percent agreement (NPA) were calculated compared with culture. Results: There were 243 HSV positive subjects, with 84 HSV-1 (51 female, 33 male) and 167 HSV-2 (85 female, 82 male) positive subjects, among 408 evaluable participants (205 female, 203 male). The sensitivity and specificity of the cobas ® HSV 1 and HSV 2 Test compared the Reference Method for HSV-1 was 92.9% (78/84) and 98.8% (320/324), respectively, and for HSV-2 was 97.0% (162/167) and 94.6% (228/241), respectively. The PPA and NPA of the cobas ® HSV 1 and HSV 2 Test compared to the culture for HSV-1 was 100% (67/67) and 93.9% (199/212), respectively, and for HSV-2 was 99.2% (128/129) and 83.2% (232/279), respectively. Conclusion: The cobas ® HSV 1 and 2 Test displayed excellent performance compared to the combined results of culture and Sanger sequencing. The test is highly suitable to detect HSV in clinician-collected anogenital swab specimens from patients with suspected HSV infection. Disclosure of interest statement: This clinical trial study was supported by Roche Molecular Diagnostics.